Adaptation Strategies of Chili Farmer Households in Dealing with Covid-19 - Baiq Yulfia Elsadewi Yanuartati; Khazlinatul Watan; Nuning Juniarsih; Ni Made Wirastika Sari (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the adaptation strategies of chili farmers' households in dealing with the impact of Covid-19 and the reasons for choosing this strategy in East Lombok Regency. The method used in this research is descriptive method. The unit of analysis in this study is chili farmer households in East Lombok Regency. The data in this study was obtained using in-depth interviews and documentation techniques. The data analysis used in this study consisted of several stages, which are data tabulation, data presentation and conclusion drawing. The data obtained in this study were processed using a descriptive data analysis technique. The results of this study indicate that the adaptation strategies carried out by chili famers’ households in dealing with the impact of Covid-19 in East Lombok Regency, are active strategies, passive strategies and network strategies. In making decisions, farmers in this study have their own reasons for choosing each strategy.